Организационная культура и ее совершенствование; Молодежный научный форум; № 5 (23) - Шарина А. С. Алена Сергеевна; Байгильдина Ю. А. Юлия Анатольевна; Чагина Е. В. Екатерина Васильевна; Деркач А. И. Алёна Игоревна; Вторушин Н. А. Николай Анатольевич (Психология, 2015)
Заглавие с экрана